Risk factors for anastomotic leakage and stricture following rectal cancer surgery: A retrospective cohort study - Arif Usta, Mehmet; Burak Cekic, Arif (Annals of Medical Research, 2021)
Aim: Anastomotic problems including anastomotic leakage and stricture following rectal cancer surgery are complications with indefinite risk factors. It was aimed to evaluate preoperative and postoperative risk factors for anastomotic leakage and stricture in patients who underwent rectal cancer surgery.Materials and Methods: Patients who underwent surgical treatment after neoadjuvant treatment for middle and distal rectal tumors were retrospectively analyzed between January 2016 and September 2019. All consecutive patients who were older than 18 years and treated via low anterior resection with colorectal anastomosis or intersphincteric resection with coloanal anastomosis with diverting ileostomy were included. Patients with and without any anastomotic complications were grouped as Group 1 and 2, respectively. Subgroup analysis based on anastomotic leakage and stricture was also performed. Results: There were 62 patients with a mean age of 60.5±12.2 years. Anastomotic complications occurred in 11 patients (17.7%). There were seven (11.3%) anastomotic leakage and six (9.7%) anastomotic stricture. Male patients were significantly higher in Group 1 (p=0.018). Anastomotic leakage was seen more commonly in male patients (p=0.035). Intersphincteric resection with hand-sewn coloanal anastomosis and the diameter of the tumor was significantly associated with anastomotic leakage (p=0.002 and p=0.004, respectively). Multivariate analysis revealed that male sex for the development of any anastomotic complication, and handsewn coloanal anastomosis, and tumor diameter for anastomotic leakage were independent risk factors. Conclusion: Male sex, intersphincteric resection with coloanal anastomosis, and diameter of tumor can be significant risk factors for the development of any anastomotic complication including anastomotic leakage following rectal cancer surgery.